abc = 38
(7x)(2x - 27) This means multiply the '7x' to each term in the other set of brackets. Hence 14x^2 - 189x
20 + 7x
(3b + 7x)(3b + 7x) or (3b + 7x)2
8y-7x
+ 27 =
8x + 33 = 7x + 27 Subtract 7x from both sides: x + 33 = 27 Subtract 33 from both sides: x = -6
(5x - 3)(7x + 9)
-7x + 6 + 7x - 2 = 4
abc = 38
(7x)(2x - 27) This means multiply the '7x' to each term in the other set of brackets. Hence 14x^2 - 189x
20 + 7x
(7x - 4)(7x + 4).
(3b + 7x)(3b + 7x) or (3b + 7x)2
8y-7x
Add 7x to each side: 136 = 27x + 20 Subtract 20 from each side: 116 = 27x Divide each side by 27: x = 116/27 = 4 & 8/27.
x2+7x+12